Optimisation of evaporator performance with adaptive superheat algorithm using fuzzy logic control for container refrigeration - Chia, Peng Kiang. (2009)
This thesis presents the application of fuzzy logic control, using an electronic expansion valve, to control refrigerant flow in a commercial container refrigeration system. Test results comparing conventional proportional-integral and derivative (PID) control versus fuzzy control have shown that fuzzy control performs better in terms of smaller overshoot of the superheat and faster settling time of the superheat response during the evaporator load pulldown mode. A better coefficient of performance (COP) was obtained with the use of the electronic expansion valve (EEV) together with a microprocessor to control a constant superheat, compared to the conventioanl thermostatic expansion valve (TEV), which is limited in terms of delivering a stable and accurate superheat control, as well as in responses to changes in operating conditions